Land Testing Service Ordering Information System with Extreme Programming Method - Khaerul Azhar; Dewi Ayu Nur Wulandari (STMIK PONTIANAK, 2022)
Information Systems can support the implementation of activities in an organization. One example of the use of Information Systems in organizations is the application of technology in the form of information systems in ordering soil testing services at the Civil Engineering Laboratory of Pakuan University. The information system is needed to assist in ordering soil testing services to produce information that is fast, precise, accurate, and efficient. The software development model used in the creation of the information system is Extreme Programming using PHP and MySQL programming languages for database creation. The Extreme Programming method is used because the method is a software development model that tries to simplify various stages in the development process so that it becomes more adaptive and flexible. The information system for ordering soil testing services at the Civil Engineering Laboratory of Pakuan University was built can manage the data needed in the soil testing order process such as inputting test category data, input customer data, and inputting transaction data ordering soil testing services and printing the required reports. This Information System also has features that make it easier for customers to input on the testing service order form and can print proof of order which also contains reports of test results that have been carried out to make it easier when customers want to see the results of soil testing that has been carried out without having to come directly to the laboratory.